Composição química e atividade biológica de Vanilla palmarum e Lippia alba - Jesus, Ingrid Medeiros de Oliveira (2018)
Vanilla palmarum and Lippia alba are plants that can be found in the semi-arid region of Bahia. Both are used for medicinal purposes by local populations, in different ways. However, V. palmarum is not much studied in several aspects, such as its chemical composition and the biological activities that it performs. L. alba, on the other hand, is one of the most studied vegetal species, but, due to its geographical variability, the chemical composition of its essential oil is quite variable. Therefore, the objective of this work was to analyze the chemical composition, antioxidant activity and antidermatophytic activity of the crude extracts of V. palmarum, as well as the chemical composition and antidermatophytic activity of the essential oil of L. albacultivated in Feira de Santana. Dermatophytes used were Trichophyton mentagrophytes, Trichophyton rubrum and Microsporum gypseum. The inhibition of mycelial growth of all fungi was evaluated and minimum and minimum fungicidal inhibitory concentrations of extracts and oil were determined. The antioxidant activity of the extracts was evaluated by free radical sequestration methods. The extracts of V. palmarum presented antioxidant activity. Both the extracts and the essential oil presented antidermatophytic activity. Carvone and limonene are the major compounds of theanalyzed essential oil